TINGKAT KEPUASAN PELANGGAN TERHADAP LAYANAN PENDIDIKAN DI SD INTEGRAL LUKMAN AL-HAKIM JEMBER - Bahar Agus Setiawan (Universitas Muhammadiyah Jember, 2018)
The level of customer satisfaction in the world of education has long been a necessity. The difference between private and public schools is no longer significant. Competition and competitive nature of private and public schools require new changes and conceptions where management of educational institutions is concerned. The implementation of a full-day-school system in Indonesia cannot be separated from the phenomena related to ‘superior schools’ back in the 1990s—many of which were pioneered by private schools, especially those that were motivated by implementing Islamic values. Such schools are usually referred to as schools that focus primarily on the quality of the teaching and learning processes rather than on the quality of students input. Today, full day school has become a trending topic or, in the language of information technology, viral in conjunction with the mandate from the Minister of Education and Culture no 23/2017 relating to School Days. Full day schools are increasingly popular and recognized by the wider community. This study employed a survey method involving a quantitative approach. Respondents were 69 students and 90 parents. The instrument used for data collection was a questionnaire consisting of 43 questions for students and 51 questions for parents. The findings of this study revealed that the level of student satisfaction for basic educational services provided by Integral Lukman Al-Hakim primary school Jember reached 99.9% with 52.17% were very satisfied and 47.82% were quite satisfied. Meanwhile, the level of satisfaction of parents reached 84.45%. with 16.67% were very satisfied and 67.78% were quite satisfied. The remaining 15.55%, however, were not satisfied. Finally, it is concluded that the level of customer satisfaction with regard to the educational services provided by Integral Lukman Al-Hakim primary school is high.